The persistence of inflation in Switzerland: Evidence from disaggregate data - Simone Elmer; Thomas Maag (ETH Zurich, KOF Swiss Economic Institute, 2009)
This paper investigates persistence of Swiss consumer price inflation using aggregate and disaggregate inflation data covering 1983-2008. We document that persistence of sectoral inflation rates is below persistence of aggregate inflation. Our main finding is that inflation persistence significantly declines in the early 1990s. An estimated factor model reveals that inflation persistence stems from a persistent component that is common to inflation rates across sectors. Both the relevance and the persistence of the common component decline over time. Depending on the sample period and aggregation level, 70 to 90 percent of the variance in sectoral inflation rates is accounted for by short-lived sectoral factors.
Keywords: E31; E52; C22; 330; inflation persistence; inflation dynamics; aggregation and persistence; Inflation; Volatilität; Schweiz